Identifikasi Karakteristik Dan Pola Gangguan Pada Sistem Distribusi 20 Kv Di Wilayah Surabaya - Perpustakaan UGM, i-lib ([Yogyakarta] : Department of Chemistry Gadjah Mada University, 2000)
This paper presents an identification of characteristics and patterns of disturbance in the 20 kV East Jawa Distribution System, especially in the Surabaya area. The disturbance itself is limited for those which influence the Power Quality of the distribution system in a steady-state condition: low power factor, under/over voltage, voltage imbalance, harmonics, and outage. The identification was obatined by field observations on the disturbance parameters: type, source, intensity, frequency, and the time the disturbance occurs for industrial, commercial, and residential loads. The identification process is one of the efforts for analyzing the existence of the disturbance and the power quality in the 20 kV Surabaya Distribution System. Observations were made on a number of feeders for each type of load, and showed that most of the disturbances were in the range of standards owned by the utility company. A few feeders supplying industrial loads, however, showed violations of standards for voltage total harmonic distortions (13.5%), low power. factor (0.76), and over voltage (21.2kV).